Flipping situations and ending plots: An approach to coherence in humour - Viana, Amadeu (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Recent linguistic research on humour and conversation has been successfully achieved on pragmatic and sociolinguistic grounds. My contribution should try to follow this (bi)methodological trail, deepening on the study of conversation and its implications. I should call Contextual Contamination (CC) the procedure of linking together different arguments and scripts in spontaneous talk. CC not only would follow from the well known given-new information opposition in talk, but would trigger comical sequencing and colloquial thinking aswell. My second step would undertake Douglas (1975a; 1975b) analysis on situational coherence in humour. I will approach some issues about mock attack theory and the collapse of pressuposed script in practical situations. My last point will approach the narrative constituent of comical performance. Absurd narratives (non comical) also confront the notional order embedded in natural stories, and we would try to grasp how this contrast works. My conclusions will draw together the narrative and the conversational dimensions of humour.